Peran Spiritualitas terhadap Forgiveness pada Karyawan Emerging Adulthood yang Mengalami Bullying di Lingkungan Kerja: Penelitian - Nelda Rachel Manao; Agoes Dariyo; Hanna Christina Uranus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to examine the role of spirituality on forgiveness among emerging adulthood employees who experience bullying in the workplace. The research background is based on the phenomenon of high workplace bullying rates in Indonesia, where 73% of workers have experienced unpleasant treatment. Emerging adulthood employees (18-29 years) who are building their professional identity become a vulnerable group to the psychological impacts of bullying. Spirituality was selected as a predictor variable as it is considered capable of being a source of internal strength in facilitating the forgiveness process. This research employed a quantitative method with a survey approach, involving 100 emerging adulthood employees who had experienced workplace bullying. Data collection used the TRIM-18 scale to measure forgiveness and a spirituality scale adapted from Burkhardt (1993). Data were analyzed using Pearson Product Moment correlation with SPSS. The results showed a significant positive relationship between spirituality and forgiveness (r = 0.741, p < 0.05) with a contribution of 54.9%. The study concludes that spirituality plays an effective role in enhancing forgiveness ability among emerging adulthood employees experiencing bullying and can be integrated into psychological intervention programs in the workplace.